COMPETENCIES OF DIGITAL MEDIA PRODUCERS IN THE CONTEXT OF THAI SOCIETY - Euajarusphan, Adipon; แสนทวี, กฤชณัท (Thai Interdisciplinary and Sustainability Review, 2024)
This research investigates the competencies of media producers in the digital age within Thai society, aiming to understand these competencies and explore ways to develop them. Conducted as qualitative research, data were gathered through in-depth interviews with media and communication scholars, as well as successful digital media producers. The analysis followed a typological approach, examining communication process components and synthesizing findings based on Zeng (2020)'s framework. The study identified eight key competency dimensions with 74 characteristics in total, encompassing rights and duties, development potential, global understanding, skills and thinking processes, morality and ethics, business capability, creativity, and information accuracy.